Epizootic outbreak of influenza A / H5N1 among wild and farm birds in the vicinity of Komsomolsk‐on‐Amur in the autumn of 2022 - M. Yu. Shchelkanov; M. N. Dunaeva; A. A. Belik; M. V. Getke; A. B. Pott; I. S. Chalenko; O. V. Iunikhina; I. E. Dombrovskaya; D. V. Pankratov (Юг России: экология, развитие)
Aim of the work was to investigate an epizootic outbreak in the vicinity of Komsomolsk‐on‐Amur (Khabarovsk Territory) in October 2022 among wild and agricultural birds.Material and methods included analysis of epizootic data, pathologic and anatomical examination of the carcasses of dead birds, collection of field material and its transportation to the laboratory without breaking the cold chain, indication of influenza A virus RNA using real‐time PCR, isolation of viral strains on a model of developing chicken embryos with subsequent assessment of virus activity using a hemagglutination reaction and infectious titer in the a swine embryo kidney cell line, sequencing of complete genome of isolated viral strains using nanopore and Sanger technologies followed by bioinformatics analysis procedures.Results obtained show that epizootics among wild birds began in February 2022 and the mass death among chickens at the Komsomolskaya poultry farm was accompanied by the death of wild birds in its vicinity. Using molecular genetic diagnostic methods it was found that etiological agent of epizootic was the influenza A virus of the H5 subtype. Seven strains of influenza A virus were isolated, the analysis of the complete genome of which allowed them to be classified as highly pathogenic variants of the genetic subgroup 2.3.4.4b of H5N1 subtype.Conclusions: East Asia including the Russian Far East retains the status of a center of genetic diversity of the highly pathogenic influenza A H5Nx virus, where the virus circulates among local bird populations and there is a high probability of reassortations between different variants the virus. Such a situation requires constant vigilance on the part of supervisory authorities, strict compliance with the requirements of biological safety by institutions and organizations engaged in agriculture and environmental management as well as regular ecological and virological monitoring in the region.